Ambulance shortest path problem by using link-based algorithm - Lee, Chooi Hua (2015)
This study was done determine the shortest route of the ambulance from the scene to the hospital. Besides that, it was done to assigns the hospital to deploy the ambulance to the scene according to the needs of the patient. In addition, the study was done to minimize the response time in terms of distance by the ambulance to transfer the patient from the scene to the hospital. The link-based algorithm was executed to determine the ambulance shortest path from the scene to the hospital. It is initiated and analyse repeatedly until the ambulance reaches the hospital as it will update the route from time to time with the traffic condition. The ambulance shortest paths from different scenes to the hospital were determined and analysed. Several alternatives to the hospitals had been executed to minimize the response time depending on the traffic condition. The link-based algorithm helps to update the paths to the hospital from time to time depending on the traffic condition. It is recommended to apply the ambulance shortest paths problem with the geospatial informatics system and the traffic transmitter for future research to improve the performance of ambulance service.